Clinical and pathological features of hair coat abnormalities in curly coated retrievers from UK and Sweden. (December 2016) - Bond, R.; Varjonen, K.; Hendricks, A.; Chang, Y. M.; Brooks Brownlie, H.
Abstract : Objectives: To gain information on hair loss amongst curly coated retrievers by questionnaire and to define the clinical and pathological features of hair coat abnormalities in affected dogs in the United Kingdom and Sweden. Materials and Methods: Questionnaires were completed by members of the Curly Coated Retriever Clubs. Fourteen dogs (six in the United Kingdom, eight in Sweden) were clinically examined and skin/hair samples collected for microscopy and histopathology. Blood was collected for haematological, biochemical and endocrine assays. Results: Of 90 dogs surveyed, 39 had current or previous episodes of symmetrical, non‐pruritic alopecia and or frizzy coat changes, usually affecting caudal thighs, axillae, dorsum and neck before 18 months of age; 23 dogs had a waxing/waning course. Examined dogs generally matched the pattern described in questionnaires. Hair shaft anomalies comprised occasional distorted anagen bulbs (10 dogs) and transverse fractures (8 dogs). Vertical histopathological sections showed infundibular hyperkeratosis (28 of 30 sections) and low‐grade pigment clumping (17 of 30). Subtle telogenisation of hair follicles was unequivocally confirmed by transverse histomorphometric analyses. Clinical Significance: The follicular dysplasia of curly coated retriever reported here is similar to that of Irish water spaniels and Chesapeake Bay retrievers but distinct from that of Portuguese water dogs. The genetic basis requires further assessment.